Performance of multichannel fiber optic parametric amplifier - Mohd Noor, Nor 'Izzati (2015)
Optical networks have a significant role to play in the present and future global telecommunication networking scenario due to the increasing demand for larger transmission capacity. In fiber optic communication systems, Dense Wavelength Division Multiplexing (DWDM) is very popular in which multiple optical signals at various wavelengths are combined and transmitted through a single fiber. DWDM technology provides a cost effective deployment strategy. One of the key components in DWDM system is an optical amplifier. Fiber optical parametric amplifier (FOPA) can be used for several signal processing application including optical amplification, phase conjugate and wavelength conversion. FOPA operate based on a fiber nonlinearity known as four wave mixing (FWM). Fiber optical parametric amplifiers are based on the third-order susceptibility of the glasses making up the fiber core. It happens when at least two waves with the different frequencies co-propagate in the fiber. In this simulation is to show the ability of a single pump parametric amplifier in the eight channels DWDM transmission system and performance of FOPA in order to ensure higher level of amplification coped with less amplifier produced signal impairments. The simulation were done by software OptiSystem 13, the fiber optical amplifier is perform by simulation of 10 Gbit/s each channel. Furthermore NRZ encoding technique, intensity OOK modulation format has been used in this simulation. The frequencies of channel carrier was chooses in the region from 193.1 THz to 193.8 THz. Eight modulated signal are transmitter over 220 km span long single mode fiber. The single pump combination with four signal radio frequency, 180 MHz, 420 MHz, 1.087 GHz and 2.133 GHz are used to show higher level of amplification and mitigating the impact of simulated Brillouin scattering. As a result, the maximum 22.134 dB gain and lower noise figure 2.84 dB is achieved.